Unicameral bone cyst in the pelvis: report of a case treated by placement of screws made from a composite of unsintered hydroxyapatite particles and poly-l-lactide - Sakamoto, Akio (Rare Tumors, 2019)
Unicameral bone cysts are fluid-filled benign lesions that occur mostly in the long bones. Unicameral bone cysts in the pelvis are extremely rare. Continuous decompression using titanium or hydroxyapatite screws has been reported as a treatment. Screws made from a composite of unsintered hydroxyapatite particles and poly-l-lactide can be used for the treatment. An adolescent male patient presented with a unicameral bone cyst in the ilium extending to a region adjacent to the hip joint. As initial treatment, the cortex was fenestrated when the patient was 13 years old and β-tricalcium phosphate implanted. The cyst first reoccurred when the patient was 15 years old and again when he was 17 years old. During the most recent treatment, unsintered hydroxyapatite particles and poly-l-lactide composite screws were placed, and no recurrence was observed during 2 years of follow-up. The slow biodegradability and absorbability of the screws may allow continuous drainage of unicameral bone cysts.